2010
DOI: 10.1002/pros.21307
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between circulatory, local prostatic, and intra‐prostatic androgen levels

Abstract: These results indicate that local prostatic DHT production has an influence on systemic serum DHT levels. Moreover, our results support the evidence that the prostate is the main DHT producer and that UGTs are important in the intra-prostatic regulation of androgens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…It is therefore tempting to speculate that the loss of this induction is likely involved in the phenotypic changes allowing tumor cells to proliferate in the presence of low androgen levels, as observed in CRPCs (8). This idea is supported by the inverse relationship existing between UGT2B15 and UGT2B17 expression and androgen-dependent prostate cancer cell proliferation (14) and by the strong influence that UGT2B15 and UGT2B17 polymorphisms exert on tissue androgen levels (36). The loss of UGT genes' sensitivity may allow prostate cancer cells to maintain sufficient DHT levels to activate AR and its regulated genes in CRPCs (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore tempting to speculate that the loss of this induction is likely involved in the phenotypic changes allowing tumor cells to proliferate in the presence of low androgen levels, as observed in CRPCs (8). This idea is supported by the inverse relationship existing between UGT2B15 and UGT2B17 expression and androgen-dependent prostate cancer cell proliferation (14) and by the strong influence that UGT2B15 and UGT2B17 polymorphisms exert on tissue androgen levels (36). The loss of UGT genes' sensitivity may allow prostate cancer cells to maintain sufficient DHT levels to activate AR and its regulated genes in CRPCs (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that UGT2B17 CNV was associated with AAG levels in subjects of European descent. Olsson et al (2011) showed that AAG levels were significantly associated with the UGT2B17 CNV, suggesting that the UGT2B17 CNV genotypes are significantly associated with AAG levels. Thus, the relationship we observed between UGT2B17 CNV and AAG levels in Whites is consistent with the two previous reports.…”
Section: Ugt2b Variants: Aag Levels and Prostate Cancer Riskmentioning
confidence: 95%
“…In addition, a polymorphism in the regulatory region of the UGT2B17 gene has been associated with altered levels of AAG (Hu et al, 2010). While both the UGT2B17 and UGT2B15 polymorphisms are significantly associated with AAG levels in European populations, no observations have been made in individuals of African descent (Hsing, 2001;Swanson et al, 2007;Olsson et al, 2011).…”
mentioning
confidence: 99%
“…DHT may have been sulfonated 29 for paracrine reuse or metabolized to androstanediol or AND in BP or CaP tissue. AND and androstanediol can be glucuronidated and trafficked from tissue, 30 but glucuronidated metabolites may have been expelled more efficiently by BP than CaP cells. Oesterling et al 31 reported that adrenal androgens produced by the adrenal gland were not sufficient for prostate growth and development in men diagnosed with hypogonadotropic hypogonadism.…”
Section: Discussionmentioning
confidence: 99%